Evaluasi Kesesuaian Penggunaan Obat Antituberkulosis Pada Pasien Tuberkulosis Paru - Lili Musnelina; Elvina Triana Putri; Jenny Pontoan; Syifa Nadila Putri (JURNAL FARMASI DAN MAKANAN, 2024)
Tuberculosis, caused by the bacterium Mycobacterium tuberculosis, primarily affects the lungs. This study aims to evaluate the precise use of antituberculosis drugs, focusing on factors such as patient suitability, correct indication, drug selection, dosage, administration method, and treatment duration. Sampling involved Purposive Sampling of pulmonary tuberculosis outpatients Dr. RSUD. H. Abdul Moeloek Bandar Lampung from January to December 2021, resulting in 89 patients. The data showed a majority of male patients, with 52 (58.4%) aged between 36 and 45 years, and 24 (26.9%) weighing between 46 kg and 55 kg. Additionally, 50 patients (56%) tested positive for sputum BTA and had undergone category I treatment previously. Evaluation of antituberculosis drug usage in these outpatients revealed 100% accuracy in patient suitability, indication, drug selection, dosage, and administration method, with a treatment duration of 15 days. Hence, it can be inferred that the utilization of antituberculosis drugs is appropriate.